1990
DOI: 10.1002/bip.360290130
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic pentapeptides as models for reverse turns: Determination of the equilibrium distribution between type I and type II conformations of Pro‐Asn and Pro‐Ala β‐turns

Abstract: Cyclic pentapeptides are excellent models for reverse turns and have been used extensively in our laboratory to explore the influence of different amino acid sequences on turn preference. This paper is divided into two parts: In the first, we review our previous studies of cyclic pentapeptides. We summarize work that demonstrates the range of conformations possible within the cyclic pentapeptide backbone, the importance of sequence chirality in determining the backbone fold, and the utility of these cyclic pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
88
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 47 publications
5
88
0
Order By: Relevance
“…The linear precursors were prepared using either a preloaded Fmoc-Gly trityl resin (2, 5, and 10) or a 2-chlorotrityl chloride resin for the loading of the N-Fmoc ω-aminocarboxylic acids (6)(7)(8)(9). Cleavage from the resin was facilitated using hexafluoroisopropanol and the side-chain protected peptides were cyclized using PyBOP followed by global deprotection using TFA.…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The linear precursors were prepared using either a preloaded Fmoc-Gly trityl resin (2, 5, and 10) or a 2-chlorotrityl chloride resin for the loading of the N-Fmoc ω-aminocarboxylic acids (6)(7)(8)(9). Cleavage from the resin was facilitated using hexafluoroisopropanol and the side-chain protected peptides were cyclized using PyBOP followed by global deprotection using TFA.…”
Section: Chemistrymentioning
confidence: 99%
“…1,2 In addition to the developmental and physiological role of CXCL12/CXCR4, CXCR4 has been shown to be involved in a number of pathological conditions, including HIV, cancer, and rheumatoid arthritis. 3 Consequently, CXCR4 has emerged as an attractive drug target, and several smallmolecule CXCR4 antagonists have been described in the literature over the last decade, 3,4 including Small cyclic peptides, such as cyclopentapeptides, are known to mimic peptide turns, 6 i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As a test of this hypothesis, a pentapeptide containing a Pro-Arg sequence was tested as a PRMT1 substrate in a linear and in a cyclic form. The cyclization of short proline-containing peptides is known to stabilize reverse turns with the proline in the i + 1 position, thus putting the neighboring arginine into the i + 2 position (Pease and Watson , 1978 ;Holl ó si et al, 1987 ;Stradley et al , 1990 ;Kumaki et al , 2001 ). In fact, the cyclization of the pentapeptide led to a 15-fold increase in k cat and a 6-fold increase in k cat / K m for PRMT1-dependent methylation.…”
Section: The Problem Of Prmt Substrate Specificitymentioning
confidence: 99%
“…Even if they show characteristics of some secondary structure, they may exist as a mixture of conformational populations, including extended forms. 5 In order to see if the observed NOE cross-peaks and the hydrogen-bond information alone can produce any reasonable structure, we applied the distance geometry calculations to the present system without using the energy term. This is equivalent to searching a structure which satisfies all the NMR data but may not necessarily be energetically favorable.…”
Section: Structure Determinationsmentioning
confidence: 99%
“…4 Structural studies on cyclic model peptides have also shown that Pro-Asn combination promotes the formation of /)-turns especially in non-aqueous solvents. 5 In addition to the immunogenical importance, the above specific sequence is also of 1 To whom correspondence should be addressed.…”
mentioning
confidence: 99%